CODE SWITCHING AND CODE MIXING IN ENGLISH LANGUAGE STUDIESâ SPEECH COMMUNITY: A SOCIOLINGUISTICS APPROACH - Wartinah, Ni Nyoman (Berumpun, 2018)
Enormously complex and not well understood are some state of affairs for a bilingual to âchangeâ theuse of language from one to another when having conversation with other bilinguals in dailyconversation. This linguistics behavior of changing the language, or widely known as âlanguageswitchingâ and âlanguage mixingâ, leads the researchers to find out the trigger behind this phenomenon.After done a research on Malaysian pre-school students, Karen Kow (2003) proposed some reasons ofdoing code switching and code mixing namely lack of one word in either language, to avoidmisunderstanding, to make a point, etc. However, students of graduated students of English LanguageStudies of Sanata Dharma University can be categorized as bilingual or multilingual since they employtwo even many languages in the daily conversation in their speech community. Therefore, by taking 12students of A class as the subject of the research through random sampling method, the discussion ofthis research will focus on investigating the reasons of both code switching and code mixing.